Improving police integrity in Uganda: Impact assessment of the police accountability and reform project - Wagner, Natascha; Hout, Wil; Namara, Rose (Review of Development Economics, 2020)
Uganda and in particular the Ugandan police are perceived as highly corrupt. To address the integrity of police officers, an intervention called the Police Accountability and Reform Project (PARP) was implemented in selected police districts between 2010 and early 2013. This paper studies the impact of PARP for a sample of 600 police officers who were interviewed about police integrity by means of 12 hypothetical vignette cases depicting context-specific, undesirable behavior of varying degrees of severity. The assessments of the cases by the police officers are analyzed using propensity score matching, inverse probability weighting, and seemingly unrelated regression techniques. We show that the self-selection of police officers into the program is unlikely to drive the results. The results suggest that officers participating in PARP activities (1) judge the presented cases of misconduct more severely, (2) are more inclined to report misconduct, and (3) also expect their colleagues to judge misbehavior at the police level more critically although the latter two coefficient estimates are smaller in size.
Keywords: police integrity; police accountability; Uganda